2024
DOI: 10.1021/jacs.3c12446
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal-Assisted In Situ Phase Reconstruction Enables Efficient and Stable 2D/3D Perovskite Solar Cells

Zonglong Song,
Yuping Gao,
Yu Zou
et al.

Abstract: Perovskite solar cells (PSCs) that incorporate both two-dimensional (2D) and three-dimensional (3D) phases possess the potential to combine the high stability of 2D PSCs with the superior efficiency of 3D PSCs. Here, we demonstrated in situ phase reconstruction of 2D/3D perovskites using a 2D perovskite single-crystalassisted method. A gradient phase distribution of 2D RP perovskites was formed after spin-coating a solution of the 2D Ruddlesden−Popper (RP) perovskite single crystal, (DFP) 2 PbI 4 , onto the 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The obtained 2D/3D film exhibited reduced trap density, increased carrier mobility, and superior moisture resistance. The optimized 2D/3D devices achieved a champion PCE of 24.87% with a high V oc of 1.185 V. The unencapsulated solar cells demonstrated considerably enhanced operational stability (>97% retention after continuous irradiation for 1500 h) [180].…”
Section: Organic Molecule Inducing Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained 2D/3D film exhibited reduced trap density, increased carrier mobility, and superior moisture resistance. The optimized 2D/3D devices achieved a champion PCE of 24.87% with a high V oc of 1.185 V. The unencapsulated solar cells demonstrated considerably enhanced operational stability (>97% retention after continuous irradiation for 1500 h) [180].…”
Section: Organic Molecule Inducing Methodmentioning
confidence: 99%
“…Crystal interface inducing method. Crystal interface inducing method was proposed to fabricate 2D/3D PSCs with high 2D crystal stability and efficiency of 3D PSCs [180]. Yang et al demonstrated in situ phase reconstruction of 2D/3D PVKs using a 2D PVK single-crystal-assisted method via the gradient phase distribution of 2D RP PVKs onto the 3D PVK surface, followed by thermal annealing.…”
Section: Organic Molecule Inducing Methodmentioning
confidence: 99%